Diagnosis of Encephalic Death in Current Peruvian Legislation - Deza Bringas, Luis (2006)
The enactment of the General Law on the Donation and Transplantation of Human Organs and/or Tissues, Law N.º 28189, and its Regulations, Supreme Decree N.º 014-2005-SA, has aroused the interest of the medical community. This is due to the approach that these regulations, especially the latter, have taken to the medical and legal determination of death. In this context, the author's analysis focuses on Title II of the aforementioned regulation, entitled "Diagnosis of death". This section sets out the guidelines and criteria for declaring death, either by the irreversible cessation of cardiorespiratory function or by the disappearance of encephalic activity, also known as encephalic death. The analysis aims to identify improvements and shortcomings in the regulations, thus contributing to the optimisation of national legislation on the determination of death and the criteria necessary for its certification. However, the study reveals some shortcomings, such as the existence of a legal vacuum with regard to specific protocols. For example, although the law provides for a protocol for verifying the irreversible cessation of encephalic function, there is no protocol for certifying cardiorespiratory death. This highlights the need to follow clear and precise protocols to ensure a correct diagnosis of death.